Adsorption Of Isoniazid Onto Sepiolite-Palygorskite Group Of Clays: An IR Study - Akalın, Elif; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Pergamon-Elsevier Science Ltd, The Boulevard, Langford Lane, Kidlington, Oxford Ox5 1Gb, England, 2010)
The adsorption of isoniazid (INH) on sepiolite, loughlinite (natural Na-sepiolite) and palygorskite from Anatolia was investigated by FT-IR spectroscopy. Experimental results indicated that INH molecules, adsorbed on sepiolite-palygorskite group of clays, are coordinated to surface hydroxyls by H-bonding interaction through the pyridine ring nitrogen lone pairs. Moreover, some of the adsorbed INH molecules may enter the interior channels of the sepiolite-palygorskite structure and involve H-bonding interaction with zeolitic water. Some intensity and frequency changes in the OH stretching band of surface hydroxyls (Si-OH) of the INH-treated sepiolite and loughlinite were observed. However, this band is found to be less affected by the adsorption of isoniazid in the case of palygorskite, probably because the surface Si-OH groups in palygorskite appear to be less abundant than in sepiolite or loughlinite. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adsorption; clays; IR spectroscopy; Isoniazid; Loughlinite; Palygorskite; Sepiolite; model-calculations; montmorillonite; loughlinite; intercalation; emme; killer; model hesaplamaları; ortaya ekleme